Effect of subgrade on leakage through a defective geomembrane seam below saturated tailings. Issue 2 (April 2023) - Fan, Jiying; Rowe, R. Kerry
Abstract: Experiments are conducted to quantify leakage through saturated tailings (with 30% fines) underlain by a geomembrane with either a 100-mm-length knife cut slit defect or a 110-mm-length defective extrusion seam. Various subgrades, a poorly graded gravel (GP) with or without nonwoven geotextile (450 or 1420 g/m 2 ) above, a well-graded gravel (GW), and a poorly graded sand (SP) are evaluated. Test results show that leakage through the slit defect and defective seam increase with the subgrade coarseness and subgrade unevenness. The inferred upper and lower bounds opening width of a slit based on the measured leakage increase with the overburden pressure and are categorized for each subgrade. Indentations in the overlapped defective extrusion seam area arise from both the entrapped materials inside the overlap and the materials underlying/overlying the geomembrane, incrementally inducing a greater interface transmissivity with the increasing stress. Overlain by tailings at total overburden pressure of 510 kPa and water head of 35m, leakage through the slit defect is 1.1L/day for SP, 2.2L/day for GW, 2.6–3.3L/day for both GP and uneven GW; leakage drops to 0.8L/day with a geotextile layer directly above the GP; leakage through the defective extrusion seam is 0.4L/day for SP and 0.8L/day for GW. Highlights: First indication of the effect of water pressure on leakage through a slit defect and inferred opening size. First evaluation of how overburden stress and subgrade affect leakage and opening size of a narrow slit or seam defect. First guidance regarding a reasonable range for the opening width of a slit defect for different subgrades. First comparison of leakage between a slit defect and defective extrusion weld.